Visualizing patterns of intervertebral disc damage with dual-energy computed tomography: assessment of diagnostic accuracy in an ex vivo spine biophantom. (August 2022) - Pohlan, Julian; Stelbrink, Carsten; Tuttle, Niklas; Kubicka, Felix; Kwon, Ho Jung; Jahnke, Paul; Goehler, Friedemann; Kershaw, Olivia; Gruber, Achim D; Pumberger, Matthias; Diekhoff, Torsten
Background: Previously, dual-energy computed tomography (DECT) has been established for imaging spinal fractures as an alternative modality to magnetic resonance imaging (MRI). Purpose: To analyze the diagnostic accuracy of DECT in visualizing intervertebral disc (IVD) damage. Material and Methods: The lumbar spine of a Great Dane dog was used as an ex vivo biophantom. DECT was performed as sequential volume technique on a single-source CT scanner. IVDs were imaged before and after an injection of sodium chloride solution and after anterior discectomy in single-source sequential volume DECT technique using 80 and 135 kVp. Chondroitin/Collagen maps (cMaps) were reconstructed at 1 mm and compared with standard CT. Standardized regions of interest (ROI) were placed in the anterior anulus fibrosus, nucleus pulposus, and other sites. Three blinded readers classified all images as intact disc, nucleus lesion, or anulus lesion. Additionally, clinical examples from patients with IVD lesions were retrospectively identified from the radiological database. Results: Interrater reliability was almost perfect with a Fleiss kappa of 0.833 (95% confidence interval [CI] 0.83–0.835) for DECT, compared with 0.780 (95% CI 0.778–0.782) for standard CT. For overall detection accuracy of IVD, DECT achieved 91.0% sensitivity (95% CI 83.6–95.8) and 92.0% specificity (95% CI 80.8–97.8). Standard CT showed 91.0% sensitivity (95% CI 83.6–95.8) and 78.0% specificity (95% CI 64.0–88.5). Conclusion: DECT reliably identified IVD damage in an ex vivo biophantom. Clinical examples of patients with different lesions illustrate the accurate depiction of IVD microstructure. These data emphasize the diagnostic potential of DECT cMaps.